Tourist Attraction Recommendation System using Analytic Hierarchy Process (AHP) - Ibrahim Al Muwahidan - NIM: 18212034 , Muhammad
Tourism is one of the most important industries in Indonesia, a major archipelago country with many natural phenomenons and diverse cultural backgrounds. This industry contributes more than 10% of Indonesia’s gross domestic product, and is projected to increase every year. On the other hand, there are a few problems regarding potential tourist attractions which are not well-known, and the current state of technology-based solutions which couldn’t portray travel planning process as humanly as possible. Therefore, a system is designed and built to recommend tourist attractions and itineraries to users automatically, with Analytic Hierarchy Process (AHP) as the method of recommendation. This system can capture the subjective preferences of the would-be tourists and set up criteria weighting based on them, then filtering the attraction types that corresponds to tourist characteristics recognized by the system. Finally, filtered attractions are ranked according to the subjective criterias before automatically generating an itinerary as an output. From the examinations that are conducted in this research, we can conclude that the recommendations made by this system drives positive results in terms of the connection between tourists’ motivation and the recommendation results, feasibility of itineraries to be realized, and the acceptance of users.